Involuntary Entry Into Consciousness From the Activation of Sets: Object Counting and Color Naming - Bhangal, Sabrina; Merrick, Christina; Cho, Hyein; Morsella, Ezequiel (Frontiers in Psychology, 2018)
High-level cognitions can enter consciousness through the activation of certain action sets and the presentation of external stimuli (“set-based entry,” for short). Set-based entry arises in a manner that is involuntary and systematic. In the Reflexive Imagery Task (RIT), for example, subjects are presented with visual objects and instructed to not think of the names of the objects. Involuntary subvocalizations arise on roughly 80% of the trials. We examined whether or not set-based entry can also occur in the case of involuntary counting. Subjects in Experiment 1A were instructed to not count the number of objects presented in an array. Involuntary counting arose on a high proportion of the trials (a mean proportion of ~ .90) for stimulus arrays having 2 to 5 objects and such counting arose less frequently across trials when the array consisted of 6 to 10 objects (a mean proportion of ~ .21). The data from Experiment 1B revealed that, when people choose to perform Set X, they also experience thoughts about an unselected Set (Set Y). Subjects were trained on one set (e.g., to ‘color name’) and then, when presented with stimuli, were given the choice to perform the trained set or a novel set. Consistent with theories proposing that the conscious contents represent several potential action plans, subjects were equally likely to experience set-related imagery or set-unrelated imagery. Our findings regarding set-based entry are relevant to many subfields of psychology and neuroscience (e.g., the study of high-level mental processes, attention, imagery, and action control).